Dichotomy between the hole and electrons behavior in the multiband FeSe probed by ultra high magnetic fields - Watson, MD; Yamashita, T; Kasahara, S; Knafo, W; Nardone, M; Beard, J; Hardy, F; McCollam, A; Narayanan, A; Blake, S; Wolf, T; Haghighirad, A; et al. (American Physical Society, 2015)
Magnetoresistivity \r{ho}xx and Hall resistivity \r{ho}xy in ultra high magnetic fields up to 88T are measured down to 0.15K to clarify the multiband electronic structure in high-quality single crystals of superconducting FeSe. At low temperatures and high fields we observe quantum oscillations in both resistivity and Hall effect, confirming the multiband Fermi surface with small volumes. We propose a novel and independent approach to identify the sign of corresponding cyclotron orbit in a compensated metal from magnetotransport measurements. The observed significant differences in the relative amplitudes of the quantum oscillations between the \r{ho}xx and \r{ho}xy components, together with the positive sign of the high-field \r{ho}xy , reveal that the largest pocket should correspond to the hole band. The low-field magnetotransport data in the normal state suggest that, in addition to one hole and one almost compensated electron bands, the orthorhombic phase of FeSe exhibits an additional tiny electron pocket with a high mobility.